O teatro de animação e o espetáculo “a canga” - CARTÁGENES , Silvana Raposo (2021)
In this dissertation I develop an analysis of the Animation Theater present in the show A Canga organized by the Laboratório de Expressões Artísticas group (LABORARTE), in the category of Theater of Actors and Puppets. I take as documentary support for the development of this analysis, fragments of notes from my observations and reports from artists, technical agents of the promoting entities and leaders of social movements that participated in the work in question and that expose the origin and materiality of the structure of the Theater of Dolls of this show. I try to understand its dramaturgy, the doll's aesthetics and political issues present in this work. The research in question reveals how the participation of this spectacle took place with the social movements that acted as support to rural workers and served as an instrument of resistance and confrontation against landlord oppression. Qualitative methodology was applied, performing a descriptive/explanatory case study based on personal and documentary records found, complemented by reports collected in online conversations and testimonials via messaging application, necessary adaptations due to the Covid 19 pandemic. This work intends to contribute to the testimony of the importance of this type of show production for the history of the Animation Theater in the heart of the Scenic Arts of Maranhão.